Exploration of mathematical concepts in prayer and Mushofahah movements - Fifi Alfi Laili; Maswar Maswar (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2024)
Knowledge of integration between mathematics and religion is necessary to increase a Muslim's mastery of scientific treasures. This article describes several mathematical concepts contained in prayer movements and Mushofahah. This research is a qualitative descriptive research type of literature review. Data/information collection methods are carried out by observation and documentation. These two methods are used to collect information about mathematical concepts contained in prayer movements and Mushofahah, obtained from several primary and secondary sources in the form of the al-Qur’an, al-Hadith, books, and scientific journals as well as documentation of prayer movements and Mushofahah (shaking hands). The data analysis technique used is content analysis. The research results showed many daily life activities, including prayer and Mushofahah, concrete examples of the integration of mathematics and Islamic religion. These concepts include: In the prayer movement, there were number concepts, which included the addition and multiplication of integers, algebraic concepts in the form of sets, arithmetic sequences, and geometric concepts in the form of lines and angles. Meanwhile, in Mushofahah, there were factorial concepts, permutation concepts, and opportunities.